When Pedal Access Is the Only Way to Save a Limb! - Radaideh, Qais; Shammas, Nicolas W. (International Journal of Angiology, 2018)
Critical limb ischemia is associated with high rates of amputation and death. Endovascular revascularization prevents amputation in approximately 80 to 90% of patients. Traditional access, however, can be a problem in some patients and pedal access may be the only way to provide adequate revascularization and potentially prevents an amputation. We present three cases to illustrate how pedal access can be the last frontier to save a leg.
Keywords: pedal access; critical limb ischemia; retrograde access